Family caregivers emphasise patience and personal growth: a qualitative analysis from the Caregiving Transitions Study. (7th February 2022) - Blinka, Marcela D; Liu, Chelsa; Sheehan, Orla C; Rhodes, J David; Roth, David L
Abstract: Background: informal caregiving for family and friends is becoming increasingly common due to the rising prevalence of chronic conditions and a shortage of affordable care options. While the impact of caregiving on caregivers' health is well-documented, nuances in caregivers' experiences may not be captured in quantitative studies. We aimed to better understand caregivers' perception of their experiences through qualitative analysis. Methods: participants were from the Caregiving Transitions Study (CTS), which is ancillary to the REasons for Geographic and Racial Differences in Stroke Study. We analysed responses from 150 caregivers to an open-ended question at the end of the CTS telephone interview concerning additional information about their caregiving experiences. We identified main themes and examined differences by sex, condition and relationship to the care recipient. Results: four major themes were identified: cultural/family expectations; growth opportunities; and reciprocity; stressors and challenges and recommendations. Male caregivers more often indicated that their motivation for taking on this role was their sense of duty towards family, while female caregivers focused on the challenges and burden of caregiving that they experienced. Overall, caregivers highlighted the importance of patience and the positive impact of caregiving, such as opportunities for personal growth, acquiring new skills, and finding fulfillment and gratitude. Conclusions: family caregivers shared both positive and challenging experiences as well as the impact that these experiences had on their lives. Understanding the full spectrum of the caregiving experience will help inform how the community and the health care system can best support caregivers in their roles.